2021
DOI: 10.3389/fpsyg.2021.671768
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Fear Affects Current Safety Behavior Mediated by Neuroticism—Results of a Large Cross-Sectional Study in Germany

Abstract: Objectives: Although many research studies concerning changes in personality and behavior in time of COVID-19 pandemic emerged, important questions still have not been answered. This study with a large sample aimed to give insights into the impact of personality on pandemic fear and behavior by investigating the Big Five traits, COVID-19-fear, and associated behavioral changes in a large German-speaking sample.Methods: About 14,048 healthy respondents (65.5% female, 34.2% male, and 0.32% other gender/gender qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…Simultaneously, highly educated individuals may have a high degree of understanding of the transmission vectors of COVID-19 and can better comply with personal protective measures (Bazaid et al, 2020). In addition, highly educated individuals can continue to maintain a high frequency of exercise during the closures caused by the pandemic (de Boer et al, 2021), and such a high frequency of exercise may make it easier for these individuals to release and relieve negative emotions, thereby allowing them to exhibit fewer symptoms such as depression and anxiety (Wolf et al, 2021). There are negative correlations among family income, hoarding behavior and negative emotions (depression, anxiety and stress).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, highly educated individuals may have a high degree of understanding of the transmission vectors of COVID-19 and can better comply with personal protective measures (Bazaid et al, 2020). In addition, highly educated individuals can continue to maintain a high frequency of exercise during the closures caused by the pandemic (de Boer et al, 2021), and such a high frequency of exercise may make it easier for these individuals to release and relieve negative emotions, thereby allowing them to exhibit fewer symptoms such as depression and anxiety (Wolf et al, 2021). There are negative correlations among family income, hoarding behavior and negative emotions (depression, anxiety and stress).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 770 adolescents in the United States ( Oosterhoff and Palmer, 2020 ) showed that the more frequently they were exposed to COVID-19-related media and disinfection practices, the higher their degree of hoarding behavior. In addition, 530 Japanese adults ( Yoshino et al, 2021 ) and the German population ( Fink et al, 2021 ) were evaluated in terms of hoarding behavior and personality traits. Multivariate regression analysis showed that individuals with high levels of agreeableness, neuroticism, openness, and cupidity tended to hoard more items during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The Big Five Inventory-10 (BFI-10) was extracted from the Big Five Inventory of 44 items to assess personality traits [ 21 ] and showed good detection performance [ 22 ]. The BFI-10 consists of 5 dimensions: extraversion, agreeableness, conscientiousness, neuroticism, and openness [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…All the scales were administered by trained collaborators with the exclusion of BFI and AQ 10 which are self-administered. MADRS is a tool used to assess the core depressive symptoms (e.g., anhedonia) [ 48 ]; HAM-D is more sensitive to detect somatic and anxiety symptoms associated with depression [ 49 ]; HAM-A is a tool that defines the severity of anxiety [ 50 ]; CGIs is a simple tool to evaluate global severity of illness [ 51 ]; BFI is a very short scale that measures the prominence of the main five personality traits (agreeableness, conscientiousness, neuroticism, extroversion, openness) [ 52 ] and finally AQ-10 is a very short questionnaire assessing the presence and prominence of autistic personality traits [ 53 ]. With regard to BFI, we focused particularly on neuroticism as the predominance of this personality trait was associated with poor mental health [ 54 ].…”
Section: Methodsmentioning
confidence: 99%